The impact of off-pump surgery in end-organ function: practical end-points. Issue 1 (December 2015) - Parissis, Haralabos; Mbarushimana, Simon; Ramesh, Bandigowdanapalya; Parissis, Mondrian; Lampridis, Savvas; Mhandu, Peter; Al-Alao, Bassel
Abstract Most surgeons perform coronary bypass surgery with the aid of cardiopulmonary bypass, which inflicts a massive systemic inflammatory response to the body leading to adverse clinical outcome. In an attempt to make CABG less invasive, interest have been diverted to the off pump technique. The current review attempts to bring an insight onto the last ten years knowledge on the off-pump impact in end organ function, with an aim to draw some clear conclusions in order to allow practitioners to reflect on the subject.